Integrasi library Json Retrofit Dengan Framework Codeigniter Pada Aplikasi UMKM UD Rahma - Wahid Hidayat; Yovi Apridiansyah; Harry Witriyono; Agung Kharisma Hidayah (UNIVED Press, 2022)
MSMEs (Micro, Small and Medium Enterprises) are businesses established by individuals / individuals / business entities that meet the criteria, MSMEs usually have limited capital, because capital only comes from business owners or a small group of people who invest capital for these MSMEs. Code Igniter is one of the widely used frameworks, where the main purpose is to minimize the code when creating a website. The advantages of Code Igniter include being open source, being able to run in all PHP versions, the program only requires few resources so that the program runs lightly and quickly, using the Model View Controller (MVC) so that it makes it easier for programmers when a website change occurs, has complete documentation, ranging from installation steps to code or functions / classes in website creation. From the results of this study, it has succeeded in integrating the JSON retrofit library in applications built for ordering products in android applications with the CI framework also successfully used to create its web-based backend application with beta test results in terms of appearance and user convenience of 72%.